2020
DOI: 10.52253/vjta.2020.v01i01.02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacteriological and Physico-Chemical Parameters of Drinking Water to Check the Efficacy of Water Purifier Systems

Abstract: Availability of safe drinking water is a prerequisite for survival and safeguard against various water-borne diseases. The study was carried out with an aim to check the efficacy of water purifier systems by assessing the bacteriological and physico-chemical parameters (temperature, turbidity, pH, TDS, chloride, total hardness, dissolved oxygen, and free CO2) in industrial RO water samples from various outlets at Maitreyi College and household RO and filtered water samples from two residential areas (Satya Nik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was found that four supply water samples (NS-3; ES-1 and CS-2, 3) from the north, east and central Delhi (Figure 2A) and five groundwater (WG-1, 2, 3; SG-4 and CG-2) samples from west, south and central Delhi have low values for dissolved oxygen (Figure 2B). A high DO level in a community water supply is good as it makes drinking water taste better (Gupta et al, 2020). Dissolved Oxygen content for drinking water should be always more than six mg/L (WHO, 2011).…”
Section: Comparative Analysis Of Do Levelsmentioning
confidence: 99%
“…It was found that four supply water samples (NS-3; ES-1 and CS-2, 3) from the north, east and central Delhi (Figure 2A) and five groundwater (WG-1, 2, 3; SG-4 and CG-2) samples from west, south and central Delhi have low values for dissolved oxygen (Figure 2B). A high DO level in a community water supply is good as it makes drinking water taste better (Gupta et al, 2020). Dissolved Oxygen content for drinking water should be always more than six mg/L (WHO, 2011).…”
Section: Comparative Analysis Of Do Levelsmentioning
confidence: 99%